Comparison of filiation by Assisted reproductive rights between Spanish and Italian (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
After a brief description of the basic aspects that structure the laws subject to comparison, are examined in particular the different cases, with respect to filiationin which the artificial insemination of a woman can take place, being the woman married with a man or a woman, joined in a heterosexual or homosexual couple, single, widow or she has survived to the man that was her husband or joined in a stableway.
Keywords: Filiation by assisted reproduction. Comparativa Law.